Purposes and principles of creating special economic zones - E. A. Velichko; V. I. Ivanova (Вестник университета)
The purposes of the research are to establish the theoretical foundations and to conduct a thorough analysis related to the creation of special economic zones (hereinafter referred to as SEZ) and identification of their key features. To achieve these purposes, theoretical aspects of SEZ have been considered in relation to Russia. As a result, the main types and distinctive characteristics of SEZ have been found, which are one of the instruments of economic development that contributes to rapid economic growth due to tax, customs and currency privileges. The article examines the process of expanding the networks of SEZ. They can act as a catalyst for changeable development. The research also studies their further formation prospects. The main results of the research lie in new knowledge about zones of special economic type, achieved by analysing the principles of creating SEZ and by collecting information about them as zones which contribute to the improvement of foreign economic relations and development of trade relations in general. The next area of research on this topic is the subsequent introduction of flexible ways to prepare the latest branches of development in the field of studying SEZ that are currently of rather great importance.